Suicidality Screening: Ensuring Providers Do Not Miss Adolescents at High Risk through Clinical Decision Support - Vundavalli, Shravani; Chandawarkar, Aarti; Beck, Kristen; Decker, Emily; Bester, Stefanie; Chaparro, Juan D.; Taxter, Alysha J. (Applied Clinical Informatics, 2025)
Major depression in adolescents is recognized as a serious psychiatric illness and a risk factor for suicide. It is important for providers to screen for depression and suicidality and have clinical decision support (CDS) for evaluation, risk assessment, and initial management. Our efforts focused on leveraging the electronic health record (EHR) to ensure that high-risk adolescents received appropriate interventions before leaving the office.This study aims to improve notification of positive adolescent depression and suicide risk screening results. Subaims include (1) designing and optimizing CDS alerts for severe depression and/or acute lethality; and (2) increasing visibility for different EHR users to avoid the near misses.We implemented several iterations of an interruptive alert after a positive mental health screening for patients aged 12 to 20 years seen in primary care and subspecialty rheumatology clinics between 2016 and 2023. Screening started with the Patient Health Questionnaire (PHQ) and Ask Suicide-Screening Questions (ASQ) on paper, and later via tablets.There were 76,919 visits during the study period, of which 50,502 (66%) completed PHQ screening. Rates of PHQ screening increased throughout the study period. Of the ASQ screenings completed, alerts were fired for 2,355 nonacute positive and 411 acute positive. In most cases, all alerts fired were more than once. Providers and clinicians receiving alerts (physicians, nurse practitioners, social workers, and psychologists) acknowledged 63 to 96% of alerts and cancelled 6 to 70% of alerts. We revised the initial alert identifying lethality to include separate alerts for major depressive symptoms and suicide risk. Iterations also included an icon on the clinic schedule and incorporated guidance on appropriate actions.By creating multiple types of alerting within different workflows, we improved notification and increased next-step visibility, leveraging decision support for patients screening positive for depression and suicidality.
Keywords: depression; suicide; mental health; clinical decision support; adolescent health